Breast cancer early diagnosis experience in Florence: can a self referral policy achieve the results of service screening?. Issue 5 (October 1994) - Giorgi, D; Paci, E; Zappa, M; Rosselli del Turco, M
Abstract : STUDY OBJECTIVE–To assess the impact of a breast clinic on a specific target population and evaluate early diagnosis performance indicators for breast cancer in the presence of a self referral policy. DESIGN–Women living in Florence between 1980 and 1989 who had undergone mammography at a self referral breast clinic were studied. Main outcome measures were the use of mammography in relation to age, symptoms, and the interval between two subsequent tests, and early diagnosis performance indicators were the detection rate (DR), the prevalence/incidence ratio, and the proportion of early detected cancers. Performance indicators were compared with those from formal screening programmes. SETTING–Florence, Italy. PATIENTS–All mammograms performed at the clinic from 1980-89 in 40-69 year old women living in Florence were examined (n = 42, 226). Records included the date of birth and of the examination, the reason for testing (asymptomatic/presence of pain/presence of symptoms other than pain), and the TNM classification for breast cancer cases. MAIN RESULTS–The total number of mammograms performed per annum increased by 70% over the decade, but much of this was routine repeat mammography (54.1% in 1989). Rates of first examinations in asymptomatic women increased in the second half of the decade from 17 per 1000 in 1985 to 31 per 1000 in 1989. Mammographic coverage decreased with increasing age from 12.6% in 40-49 year olds to 6.0% in 60-69 years old. Performance indicators of the activity in asymptomatic women were comparable with those expected in service screening. The proportion of not advanced cancers detected in asymptomatic women was 62.3% with a DR of 5.3 per 1000, and the average prevalence/incidence ratio was 2.9. CONCLUSIONS–High quality mammography performed in a breast clinic in self referred asymptomatic women can achieve as good results as a formal invitation screening service. Only a few of these women will benefit, but those who do are likely to be younger (40-49 year old women).